Prognostic Value of Coronary Artery Calcification Identified by the Semi-quantitative Weston Method in the Emergency Room or Other Hospitalized Patients - Chen, Lu; Vavrenyuk, Andrey; Ren, Jun Hong; Desai, Pankil; Bahgat, Joseph; Bernstein, Michael A.; Ebright, Michael I.; Gowda, Mamatha; Rose, Suzanne; Fallahi, Arzhang; Stainken, Brian; Hsi, David H. (Frontiers in Cardiovascular Medicine, 2021)
Background: Coronary artery calcification (CAC) may provide insight to the patients’ coronary artery disease (CAD) risks and influence early intervention. With increasing use of non-gated CT scans in clinical practice, the visual coronary artery scoring system (Weston Method) could quickly provide clinicians with important information of CAC for patient triage and management. Methods: We retrospectively studied the available CT imaging data and estimated CAC burden using the Weston method in 493 emergency room or hospitalized patients. The Weston scores were calculated by the sum of the score for each vessel including the left main, left anterior descending, left circumflex artery and right coronary artery (range 0-12). The primary endpoint was a composite of the major adverse cardiac events (MACEs), including cardiac death, myocardial infarction, stroke, and coronary revascularization. Results: During a median follow-up of 85 months, a total of 25 (5.1%) MACE were recorded and 57 (11.2%) patients died from any causes. Detectable CAC was most common (96%) in the left anterior descending coronary arteries. Multivariable analysis showed that CAC total scores were independent predictors for MACE and all-cause mortality. Receiver operating characteristic analysis showed that CAC total score≥5 was the optimal cutoff value for predicting MACEs. Conclusions: In the emergency room and hospitalized patients, the semi-quantitation of CAC burden using the Weston score system was related to the long-term cardiovascular outcomes including mortality. Clinicians and radiologists should maximize the value of non-contrast chest CT images by reporting CAC details.